Ecocardiografia em «Cor Triatriatum Dexter» - Nunes, MA (2011)
"Cor triatriatum dexter" (CTD) is an unusual cyanotic cardiac defect in which the right atrium is subdivided into two distinct chambers due to the persistence of the "sinus venosus" valve. Two patients with CTD ho were evaluated and treatment in 1979 and 1992 are described: the first one, had total anomalous pulmonary venous return to the coronary sinus or "cor triatriatum sinister" as preoperative diagnosis based on M-mode echocardiographic findings. The presence of a membrane inside the right atrium was suspected on cineangiogram. The other one had a preoperative diagnosis of CTD. Anatomic relationships and physiological effects were established by two dimensional and Doppler ultrasonography and confirmed at cardiac catheterization and surgery. High resolution two dimensional echocardiography coupled with Doppler ultrasonography has a definite role in the study of this heart defect.